Stabilizing assistance for individuals with mental disorders alongside mental health professionals - Purwasih, Galuh Dwi; Yuli Ani Setyo Dewi; Miftahillah, Miftahillah (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
A Person with a disturbed soul is a problem That is reasonably severe and needs attention, especially in the Perak sub-district realizing that the sub-district is always alert in handling this to create a mentally healthy environment. In subdistrict Silver, there is 13 Village includes, including Village Perak, Pagerwojo, Sumberagung, Kepuhkajang, Jantiganggong, Sembung, Gadingmangu, Plosogenuk, Sukorejo, Kalangsemanding, Glagahan, Temuwulan, and Cangkringrandu. Understanding family, which is minimal about maintaining the patient's soul, makes Families tend to have a negative attitude towards people with a mental health condition. This activity aims to obtain an overview of efforts to heal people with mental health conditions and the obstacles they experience. This activity involved 25 people consisting of caring families, mental health cadres, and the village government. The data collection techniques were observation, interviews, and Forum Group Interview (FGI). The intervention methods used are advocacy (advice) and psychoeducation with the Wilcoxon test (analyzing the results of paired observations from two data, whether they are different or not). In psychoeducation activities, it was discovered that participants' knowledge, understanding, and skills increased, as shown in the change in scale score from 36.25 to 39.25. Families show behavioral patterns in providing care and treatment for people with mental health conditions. Through counseling activities, a mental health post can be formed that provides services every month to the families of people with a mental health condition, one of which is Poskeswa Seroja. Through advocacy (advice) activities, a mental health post can be created to provide monthly services to the patient's family.